LITERACY AND PEDAGOGY “ THE ENGLISH VOWEL TRANSCRIPTION SYSTEMS AND THE NIGERIAN L2 LEARNER OF ENGLISH (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The paper investigated the implications of the transcription systems of the English vowels for the Nigerian learner of English. It did a comparative analysis of some transcription systems of the English vowels. It found that many of the scholars of English phonetics tend to write out the symbols of the English sounds in different forms, largely dependent on their regional background. This, it was observed, usually leads to a multiplicity of symbols to represent the same sound. The paper noted that this usually causes confusion for the Nigerian L2 learner of English. It therefore suggested that an attempt should be made to create a uniform format of vowel representations in English to help the Nigerian EL2 learner have a better and easier mastery of the English sound system.